1991
DOI: 10.1097/00006842-199107000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic amines in anorexia nervosa: circadian rhythm in urinary excretion and influence of posture and physical task load on plasma catecholamines.

Abstract: To investigate the sympathetic response in anorexia nervosa (AN) patients to stimuli occurring in normal life, biogenic amines were studied in 10 female outpatients. As control groups 10 lean and 10 normal weight healthy female subjects were included. It was hypothesized that the lean control group would have intermediate values between the AN patients and the normal weight controls. The AN patients and the lean controls had a mean underweight of 33.1% and 13.7%, respectively. For the excretion in 24-hr urine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…Similarly, in a more recent study investigating the pathophysiological correlates of migraine in patients with eating disorders, dopamine plasma levels were elevated in patients with AN when compared with those of healthy controls (D'Andrea et al, 2009). In contrast, Van Binsbergen et al (1991) showed that the influence of posture on dopamine levels was not different between AN patients and lean or normal-weight controls. They found an increased adrenal sympathetic activity and a decreased neural sympathetic activity, as evidenced by the low noradrenaline: adrenaline plasma ratio obtained during orthostasis and exercise testing.…”
Section: Plasma and Urinary Concentrations Of Dopamine And Its Metabomentioning
confidence: 74%
See 1 more Smart Citation
“…Similarly, in a more recent study investigating the pathophysiological correlates of migraine in patients with eating disorders, dopamine plasma levels were elevated in patients with AN when compared with those of healthy controls (D'Andrea et al, 2009). In contrast, Van Binsbergen et al (1991) showed that the influence of posture on dopamine levels was not different between AN patients and lean or normal-weight controls. They found an increased adrenal sympathetic activity and a decreased neural sympathetic activity, as evidenced by the low noradrenaline: adrenaline plasma ratio obtained during orthostasis and exercise testing.…”
Section: Plasma and Urinary Concentrations Of Dopamine And Its Metabomentioning
confidence: 74%
“…However, two studies found that levels are normal (Johnston et al, 1984;Van Binsbergen et al, 1991). The latter study showed that AN patients had reduced urinary dopamine, which might be because of lower protein intake (Van Binsbergen et al, 1991).…”
Section: Dopamine In Anorexia Nervosa Kontis and Theochari 501mentioning
confidence: 97%
“…18 Inexiste um consenso se as alterações encontradas nos valores de noradrenalina e seus metabólitos na AN indicam aumento ou diminuição da atividade da noradrenalina nesta doença. [19][20][21] A mesma indefinição existe para a 5-HT e seus metabólitos na AN. As concentrações séricas de 5-HT encontraram-se elevadas.…”
Section: Somáticosunclassified
“…Treatments using 5-HT-stimulating tricyclic antidepressant and specific serotonin reuptake inhibitors have generally been unsuccessful, however Gowers and Bryant-Waugh, 2004). During the active phase of AN and after recovery from the disorder, dopamine (DA) secretion has also been reported to occur, with both hypersecretion (Van Binsbergen et al, 1991;Bowers et al, 1994;Halmi, 1996;Brambilla et al, 2001;Castro et al, 2004) and hyposecretion of the amine and its metabolites (Riederer et al, 1982;Halmi et al, 1983;Owen et al, 1983;Gillberg, 1983;Kaye et al, 1984Kaye et al, , 1999Lawrence et al, 2003;Frank et al, 2005). To date, no significant correlations have been found between DA or DA receptor gene alterations and the development, course and prognosis of AN (Bruins-Slot et al, 1998).…”
Section: Introductionmentioning
confidence: 99%